2013
DOI: 10.1007/s13105-013-0272-5
|View full text |Cite
|
Sign up to set email alerts
|

Nigella sativa attenuates myocardial ischemic reperfusion injury in rats

Abstract: Myocardial ischemia-reperfusion (I/R) represents a clinically relevant problem associated with thrombolysis, angioplasty, and coronary bypass surgery. Radical oxygen species generated during early reperfusion are the primary activator of mitochondrial permeability transition pore (MPTP) opening which finally results in cardiomyocyte death. Nigella sativa (NS) has been shown to have antioxidant properties. The present study aimed to determine whether supplementation with NS can provide sufficient protection for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Ischemia/reperfusion is associated with thrombolysis, angioplasty and coronary bypass surgery which relieve myocardial ischemia, but simultaneously cause further damage to myocardial tissue, which is known as myocardial ischemia/reperfusion (MI/R) injury [1]. MI/R injury is one of the death threats in various cardiovascular diseases [2].…”
Section: Introductionmentioning
confidence: 99%
“…Ischemia/reperfusion is associated with thrombolysis, angioplasty and coronary bypass surgery which relieve myocardial ischemia, but simultaneously cause further damage to myocardial tissue, which is known as myocardial ischemia/reperfusion (MI/R) injury [1]. MI/R injury is one of the death threats in various cardiovascular diseases [2].…”
Section: Introductionmentioning
confidence: 99%
“…Endothelial barrier dysfunction and subsequent intramyocardial haemorrhage are two well-recognized responses of the microvasculature dysfunction to cardiac I/R injury, results in an increased production of reactive oxygen species and soluble inflammatory mediators [ 17 , 18 ]. We observed the emigration of red cells from microvessels and up-regulation of several inflammatory cytokines in I/R rats.…”
Section: Discussionmentioning
confidence: 99%
“…The NS-treated group showed enhanced post I/R contractile and vascular recovery, which was accompanied by elevated NAD + and decreased MDA. NS afforded substantial recovery of the post I/R cardiac functions via inhibition of mitochondrial permeability transition pore (MPTP) opening, which finally results in cardiomyocyte death 166 . ElBahai et al, reported evidence of physiological and beneficial effects of long-term NS supplementation on cardiac hypertrophy in rats 167 .…”
Section: Gastroprotective Effectsmentioning
confidence: 99%